Instruments and artisanal practices in long distance oceanic voyages. (29th May 2019) - Leitão, Henrique
Abstract : Scientific instruments are not neutral artefacts; the perception of their value is greatly determined not only by the objects themselves and the function they perform, but also by the context of their use. In the 16th and 17th centuries, scientific instruments – not only nautical ones – acquired a prominent place in European societies that greatly transcended the specific narrow professional circles that used them. This has already been noted as being an important feature in the development of science in early modern Europe. But exactly how did this happen? Following other recent studies, I argue in this paper that in order to understand this phenomenon one has to look carefully at artisanal practices of the period.